Attitudes toward seeking couples counseling among Egyptian couples: towards a deeper understanding of common marital conflicts and marital satisfaction - Attia, Eman Onsy (AUC Knowledge Fountain, 2013)
The purpose of this study was to explore factors associated with marital satisfaction and attitudes toward seeking couples counseling among affluent Egyptian couples. A total of 411 married participants answered an online survey. This study demonstrated that the most common conflicts among participants were time spent together and lack of communication. Moreover, the study results showed that higher agreement among couples was related to higher marital quality. As a result of knowing that Egypt is considered a religious culture, this study examined the relationship between religious marriage and marital satisfaction, which was found to be a positive relationship. With regards to factors that would predict higher marital quality level, none of the socio-demographic and marital factors were significant. This study also explored factors associated with more positive attitudes toward seeking couples counseling among affluent Egyptian couples. Females were found to be three points higher on the attitudes towards seeking couples counseling scale than males. Also, participants with Master’s degrees showed significant positive attitudes toward seeking couples counseling. For the barriers, “not knowing a good mental health practitioner” was found to be the most frequently selected barrier among participants. Findings of this study may help in designing better couples counseling services for Egyptian couples.